Prevalence of comorbidities and their relationship to functional status of children with cerebral palsy - Rameshan, Sruthi; Buch, Pankaj M (Indian Journal of Child Health, 2019)
Background: Cerebral palsy (CP) is the most common motor disorder in children. Associated comorbidities are very common. Gross motor functional classification system (GMFCS), manual ability classification system (MACS), and communication function classification system (CFCS) are used to decide functional ability. Functional ability and comorbidities have the greatest impact on the child with CP. There is a paucity of data regarding the functional level and their correlation with comorbidity. Objective: The aim of the study was to find the prevalence of comorbidities in CP and their correlation to functional status in children. Materials and Methods: A total of 154 consecutive children with CP attending district early intervention center and pediatric department from the period of January to December 2018 were enrolled. Cases were evaluated by history, clinical examination, and investigations. CP was classified in subtypes. Cases were screened for comorbidities. Functional assessment was done as per GMFCS-ER, MACS, and CFCS. Results: Study showed that 76% of children had spastic CP, 7% dyskinetic, 6% hypotonic/ataxic, and 11% of them had mixed CP. Mean age was 4 years. Perinatal asphyxia was the most common insult. Comorbidities were intellectual disability (81%), epilepsy (50%), visual problems (70%), hearing problems (12%), malnutrition (36%), and drooling (61%). About 63% were having GMFCS level ?3. About 60% had MACS and CFCS level ?3 with significant correlation. Comorbidities were dichotomously distributed across GMFCS levels. There was a strong correlation between comorbidity burden and GMFCS level. Conclusion: Comorbidities were significantly observed and disproportionally distributed across GMFCS levels. The burden of comorbidities was more in higher levels of GMFCS.